FARMERS’ PERCEPTION OF CLIMATE CHANGE AND ADAPTATION IN KHYBER PAKHTUNKHWA PAKISTAN: A CASE STUDY OF NOWSHERA DISTRICT - Muhammad Zafarullah Khan (Gontor AGROTECH Science Journal, 2018)
Climate change has a devastating effect on yields of major crops and is considered to become a threat to national food security. Therefore, this study was designed to explore farmers’ perception of climate change and investigate changes in seasonal temperature and rainfall over the last two decades. Focus Group Discussion (FGD) was employed to analyze the perceptions of farmers about climate change vulnerabilities and their adaptation strategies to cope with the changing climatic conditions. The results revealed that regarding environmental services, water availability was decreased due to low rainfall. In addition, the supply of firewood was also decreased due to a high demand on fuel and construction purposes. Furthermore, there was an increase in population density and a decrease in medicinal plants and wildlife due to deforestation. The temperature increased over the last 20 years and the length of the summer period was longer due to less rainfall while the duration of winter turned to be short. It is reported that the spring season is almost merged in the summer season, with the increase of temperature during the spring. Therefore, agriculture research should develop a variety of crops that can adapt to climatic extremes and educate farmers through seminars and campaigns to build their adaptive capacity dealing with the use of cultural practices to mitigate climate change.